EXPLORING FOUR DIMENSIONS OF ONLINE INSTRUCTOR ROLES: A PROGRAM LEVEL CASE STUDY - Liu, Xiaojing; Bonk, Curt J.; Magjuka, Richard J.; Lee, Seung-hee; Su, Bude (Online Learning, 2005)
The purpose of this study was to understand the practice of online facilitation in a Midwestern university which has a highly successful traditional MBA program. This study explored the instructors’ perceptions regarding four dimensions of instructor roles using Berge’s [1] classifications: pedagogical, managerial, social, and technical. This study also examined the challenges and issues confronting online instructors when fulfilling these roles. The results suggest that instructors carried out several important roles to varying degrees. The findings reveal a stronger emphasis on the pedagogical roles (course designer, profession-inspirer, feedback-giver, and interaction-facilitator). Emphasizing those roles, the instructors promote three types of interactions: student-content, student-student, and student-teacher. A lesser emphasis on social roles represented mixed feelings regarding its importance to the instructors. While students rated the instructors very positively, the results also indicate that instructors still need to have their roles transformed pedagogically, socially, and technologically if they are to establish a more engaging and fruitful environment for online learning.